HORMONAL AND GENETIC MECHANISMS OF METABOLIC-ASSOCIATED STEATOTIC LIVER DISEASE IN WOMEN OF REPRODUCTIVE AGE - Yunusova , Dilfuza; Ravzatov , Jasurbek (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
Metabolic-associated steatotic liver disease is currently one of the most pressing issues in hepatology and metabolic medicine. In addition to insulin resistance, obesity, dyslipidemia, and chronic low-grade inflammation, hormonal imbalance and genetic factors also play a significant role in the development of this disease. In particular, in women of reproductive age, special importance is attributed to estrogens, androgens, sex hormone-binding globulin, the aromatase system, as well as genes associated with steroid metabolism.